Experimental comparison of single-phase active rectifiers for EV battery chargers - Monteiro, Vítor Duarte Fernandes (2017)
An experimental comparison of single-phase active rectifiers for electric vehicle (EV) battery chargers is presented and discussed. Active rectifiers are used in on-board EV battery chargers as front-end converters to interface the power grid aiming to preserve the power quality. In this paper, four topologies of active rectifiers are compared: traditional power-factor-correction; symmetrical bridgeless; asymmetrical bridgeless; and full-bridge full-controlled. Such comparison is established in terms of the requirements for the hardware structure, the complexity of the digital control system, and the power quality issues, mainly the grid current total harmonic distortion and the power factor. Along the paper these comparisons are presented and verified through experimental results. A reconfigurable laboratorial prototype of an on-board EV battery charger connected to the power grid was used to obtain the experimental results.